Examination invigilation scheduling system system in optimising lecturers' preference / Ong Mooi Lian... [et al.] - Ong, Mooi Lian; Liew, Lee Hung; Sim Phek Kim, Jacqueline (2006)
The Examinations Invigilation Scheduling System aims to reduce manual involvement and amount of time taken by the invigilation scheduling committee in preparing the final examinations invigilation schedule. This is made possible with the creation of a database that collects information pertaining to the examinations invigilation schedule such as lecturers’ preferences and constraints of the invigilation designing process. This system is beneficial especially to the Academic Administration Office of institutions of higher learning because it enables them to produce comprehensive examinations invigilation schedule. Besides that, being computer-aided and accessible by lecturers on-line, it allows lecturers to choose their preferences, provide feedback and any other relevant information, and at the same time obtain a summary of their invigilation schedule even while away from the office. This automated way of capturing, optimising and disseminating invigilation information paves the way for the development of a systematic approach in preparing examinations invigilation schedule. With that, suitable problem-solving support system which will aid the process of computerising examinations invigilation scheduling system can be identified. This Examinations Invigilation Scheduling System has been successfully used for the past five semesters in UiTM Sarawak.